plzzzzzzz ans. the question

Asked by prasadnidhi | 24th May, 2010, 04:06: PM

Expert Answer:

 sec4θ (1-sin4θ) - 2tan2θ =

sec4θ (1-sin2θ)(1+sin2θ) - 2tan2θ =

sec4θ (cos2θ)(1+sin2θ) - 2tan2θ =

sec2θ (1+sin2θ) - 2tan2θ =

sec2θ + tan2θ - 2tan2θ =

sec2θ  - tan2θ = 1                   ... since  sec2θ = 1 + tan2θ

Regards,

Team,

TopperLearning.

Answered by  | 24th May, 2010, 05:30: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.